OurCrowd : growing a Crowdfunding platform in a VC world - Markovich, Sarit; Meagher, Evan (London : SAGE Publications Ltd, 2017)
This case features the challenges of a startup in the crowdfunding space in 2015 as its leadership assesses potential sources of growth for the companys future. Founded in Israel in 2012 by a renowned venture capitalist, OurCrowd was a venture capital crowdfunding platform that strove to connect high-growth startups raising capital with accredited private investors from around the world. Its value proposition was to democratize an inefficient market for private equity that had historically been dominated by a small number of highly connected venture capital firms (VCs). The case asks students to put themselves in the shoes of OurCrowds head of investor community as he prepares for a meeting with the companys board of directors to discuss potential strategies for growth: Should the company partner with the incumbent VCs it initially sought to disrupt, emphasize marketing its Portfolio Reserve fund, strive to provide its investors and investees with higher value-added services, target a broader swath of investors by aggressively marketing the platform in international markets, or attempt to go up-market and pursue increasingly larger deals with later-stage companies? Through assessing these options and discussing this case, students will learn about incentive problems in two-sided markets as well as how different types of crowdfunding platforms create value for users.
Originally published in Markovich, S., & Meagher, E. (2015). OurCrowd: Growing a Crowdfunding Platform in a VC World. 5-215-253. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; OurCrowd; Crowd funding; Venture capital